2006
DOI: 10.1152/ajpregu.00020.2006
|View full text |Cite
|
Sign up to set email alerts
|

High dexamethasone concentration prevents stimulatory effects of TNF-α and LPS on IL-6 secretion from the precursors of human muscle regeneration

Abstract: A frequent finding in patients surviving critical illness myopathy is chronic muscle dysfunction. Its pathogenesis is mostly unknown; one explanation could be that muscle regeneration, which normally follows myopathy, is insufficient in these patients because of a high glucocorticoid level in their blood. Glucocorticoids can prevent stimulatory effects of proinflammatory factors on the interleukin (IL)-6 secretion, diminishing in this way the autocrine and paracrine IL-6 actions known to stimulate proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 34 publications
9
41
0
1
Order By: Relevance
“…The release of cytokines, including IL-6, IL-1, IL-8, IL-10, IL-15 and TNFα (Petersen and Pedersen, 2005;Peake et al, 2005;Nielsen and Pedersen, 2008), has already been demonstrated in the skeletal muscle making it an endocrine organ actively participating through this communication in the immunoregulatory, anti-inflammatory, regenerative and metabolic effects (Delaigle et al, 2004;Mann et al, 2011). Indeed, this local production of cytokines in skeletal muscle and myocardium in response to stressors (LPS, exercise and hypoxia) can be abundant, and can contribute substantially to the amounts of these cytokines in the systemic circulation, mimicking the responses generally observed in inflammatory disease (Febbraio and Pedersen, 2002;Prabhu, 2004;Prelovsek et al, 2006;Brandt and Pedersen, 2010;Pirkmajer et al, 2011). Recent studies have revealed a strong involvement of skeletal muscle in the pathophysiology of chronic disease and its role as an important target and generator of detrimental pathophysiological processes (Filippatos et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The release of cytokines, including IL-6, IL-1, IL-8, IL-10, IL-15 and TNFα (Petersen and Pedersen, 2005;Peake et al, 2005;Nielsen and Pedersen, 2008), has already been demonstrated in the skeletal muscle making it an endocrine organ actively participating through this communication in the immunoregulatory, anti-inflammatory, regenerative and metabolic effects (Delaigle et al, 2004;Mann et al, 2011). Indeed, this local production of cytokines in skeletal muscle and myocardium in response to stressors (LPS, exercise and hypoxia) can be abundant, and can contribute substantially to the amounts of these cytokines in the systemic circulation, mimicking the responses generally observed in inflammatory disease (Febbraio and Pedersen, 2002;Prabhu, 2004;Prelovsek et al, 2006;Brandt and Pedersen, 2010;Pirkmajer et al, 2011). Recent studies have revealed a strong involvement of skeletal muscle in the pathophysiology of chronic disease and its role as an important target and generator of detrimental pathophysiological processes (Filippatos et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…The myotube cultures used were derived from primary myoblast cultures as described previously (Prelovsek et al, 2006). In brief, human muscle cells were derived from the satellite cells released from the muscle tissue, cleaned of adhering connective tissue, cut into small pieces and trypsinised.…”
Section: Preparation Of Human Muscle Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…47 TNF-α has been shown in several studies to activate muscle protein degradation directly and induces IL-6 release. 48 It has been demonstrated that IL-6 can impair TNF-α expression in cardiac muscle; one potential role of IL-6 expression in contracting skeletal muscle is therefore to downregulate TNF-α expression. 49 Llovera et al 50 demonstrated that TNF-α administration to healthy, cancer free rats brought about an enhanced rate of degradation of skeletal muscle protein, even though body weight loss was not apparent in the animals.…”
Section: Tumor Necrosis Factor Alpha (Tnf-α)mentioning
confidence: 99%
“…59 Glucocorticoids can prevent the stimulatory effects of proinflammatory factors on IL-6 secretion, which in general stimulate proliferation at the earliest, myoblast stage of muscle formation. Prelovsek et al 48 reported that a high dexametasone concentration prevents the stimulatory effects of TNF-α and LPS on IL-6 secretion from the precursors of human muscle regeneration. It results in prevention of myoblast proliferation, leading to a reduced final mass of the regenerated muscle.…”
Section: Interleukine -6 (Il-6)mentioning
confidence: 99%